Un dia de nieve - Keats, Ezra Jack. (New York : Puffin Books, 1991)
Las aventuras de un muchachito en la ciudad cuando hace mucha nieve.
The adventures of a little boy in the city on a very snowy day.
Translation of: The snowy day.
Art techniques used: Graphic, bright and patterned paper collage embellished with paints and eraser stamps.
Keywords: Snow -- Juvenile fiction; African Americans -- Juvenile fiction; Nieves -- Novela juvenil; Afronorteamericanos -- Novela juvenil; Materiales en espanol